The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1097/00007890-200202270-00017
|View full text |Cite
|
Sign up to set email alerts
|

Transplant tumor registry: donors with central nervous system tumors1

Abstract: The risk of tumor transmission from donors with CNS malignancies seems to be small. Certain tumors, such as glioblastoma multiforme and medulloblastoma, carry a high risk of transmission and should be avoided. The risk of tumor transmission should be weighed against the risk of the patient dying on the waiting list without a transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 14 publications
2
69
0
1
Order By: Relevance
“…Thus far, there have been 17 documented cases of donor-transmitted malignancies to liver transplant recipients (Table 2). 48,49 Based on these data, cancer histologies with prohibitively high transmission risk include melanoma and choriocarcinoma. The cancer-free interval must also be considered on evaluation of donors with a history of malignancy.…”
Section: Donors With Malignanciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, there have been 17 documented cases of donor-transmitted malignancies to liver transplant recipients (Table 2). 48,49 Based on these data, cancer histologies with prohibitively high transmission risk include melanoma and choriocarcinoma. The cancer-free interval must also be considered on evaluation of donors with a history of malignancy.…”
Section: Donors With Malignanciesmentioning
confidence: 99%
“…49 Donors with histories of primary central nervous system (CNS) tumors have also been evaluated. 48 Between January 1992 and December 1999, 397 of 42,340 cadaver donors had a history of CNS tumors. The 397 donors provided livers for 293 recipients, of whom 6 developed posttransplantation malignancies (two tongue, three skin, one posttransplantation lymphoproliferative disorder).…”
Section: Donors With Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, according to the UNOS registry (USA) review from 2002 of 397 donors with a history of primary CNS tumors, from whom 1220 organs were transplanted and after the follow-up of 36-months, no tumor transmission to the recipient was observed. But, UNOS itself warns that some tumors, such as multi-forme glioblastoma (GBM) and meduloblastoma, can potentially have a high transmission risk and therefore donors presenting with a history of these tumors should not be used [14]. Furthermore, Israel Penn International Tumor Registry (IPITTR) (USA) states that, when there are no risk factors (listed above) the rate of transmission from donors with primary CNS tumors to organs recipients is 7%.…”
Section: Primary Tumors Of the Central Nervous Systemmentioning
confidence: 99%
“…2 The IPITTR and isolated case reports 6,7 are responsible for the negative reputation of donors with CNS cancers. 8 Prospective, multicenter registries 9 and some large, single-center experiences, such as Kashyap et al's study, 1 have demonstrated that the risk of CNS cancer transmission should be evaluated as 0% to 3%, and these data have to be better defined by further prospective, large-scale registries. 3 In comparison with the actual, unacceptable death rates on the liver waiting lists, which have led to the development of living related liver transplantation and its 0.5% donor mortality risk 10 …”
mentioning
confidence: 99%